2003
DOI: 10.1007/s00595-003-2607-2
|View full text |Cite
|
Sign up to set email alerts
|

Nonocclusive Mesenteric Ischemia After Aorto-Iliac Reconstruction of a Ruptured Abdominal Aortic Aneurysm: Report of a Case

Abstract: We report a case of nonocclusive mesenteric ischemia (NOMI), which developed after Y-grafting for a ruptured abdominal aortic aneurysm (AAA). A 71-year-old man was referred to our hospital with severe abdominal pain and signs of shock. Computed tomography revealed a ruptured AAA, and emergency aneurysmectomy and aortic grafting were performed. However, on postoperative day 7, a large amount of pus was seen oozing from the surgical wound. An emergency laparotomy revealed segmental, highly diffuse necrotic chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Mitchell et al reported that the risk of intestinal necrosis was infl uenced more by intraoperative hypotension than by the pursuit of the IMA reconstruction. 7 This fi nding, together with the recently reported pathology known as nonobstructive mesenteric ischemia (NOMI), 8 raises concerns of reduced abdominal organ reperfusion pressure and vasospasms in conjunction with long-duration aortic clamping. In a similar case, Neglen et al used pediatric extracorporeal circulation to reperfuse the IMA at a fl ow rate of 650-900 ml/min.…”
Section: Discussionmentioning
confidence: 97%
“…Mitchell et al reported that the risk of intestinal necrosis was infl uenced more by intraoperative hypotension than by the pursuit of the IMA reconstruction. 7 This fi nding, together with the recently reported pathology known as nonobstructive mesenteric ischemia (NOMI), 8 raises concerns of reduced abdominal organ reperfusion pressure and vasospasms in conjunction with long-duration aortic clamping. In a similar case, Neglen et al used pediatric extracorporeal circulation to reperfuse the IMA at a fl ow rate of 650-900 ml/min.…”
Section: Discussionmentioning
confidence: 97%
“…It is also possible that the intestinal ischemic episode may occur due to nonobstructive causes in already hospitalized patients or during major aortoiliac reconstructions. 1,3,14 Under these circumstances bacterial translocation, sepsis, and systemic infl ammatory response syndrome occur and a vicious circle of further metabolic acidosis and subsequent circulatory and respiratory failure tend to develop, thus playing a signifi cant role in the reported high mortality rate. [15][16][17] Previous well-designed experimental studies have shown that PFC-O 2 offers a reduction in mortality and protects the intestinal mucosa from ischemia/reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…Different complications during or after an aortic clamping, in the postoperative follow up of humans [3,8,17], and in porcine models are observed. After abdominal aortic surgery humans showing cases of paraplegia, aortic occlusion with ischemic colitis, ischemic lower limbs, and non occlusive mesenteric ischemia are described [24,25]. There are also single reports about potential paraplegia after aortic cross clamping in pigs [4,13,14,21].…”
Section: Introductionmentioning
confidence: 99%